Environmental impact assessment of small scale gold mining operations in Davao del Norte - Villaluz, Maya Gabriela Q. (1988)
The Philippines is experiencing a new boom in the mining industry. This is brought about by the small scale mining activities sweeping all over the country. This study explores the significant impacts of small scale mining operations. The escape of hazardous wastes in the air and water environment, increased seismicity, land subsidence, erosion, siltation, improper land use are all possible adverse effects resulting from the exploration, development, exploitation, and processing of gold ore deposits. Each of these phases has differing impacts on the environment. The small scale mining activities in Diwalwal have been used as a case study. Findings revealed the extent of the changes on the various sectors of the environment.
Mitigation and monitoring measures have been recommended to prevent the current level of environmental degradation. To achieve this, the proper institutional arrangements must be made which include legalizing the operations of the scale scale miners, educating the miners on the proper methods of mining and processing of the gold ores, filling up of mined out workings, stabilizing slopes to control erosion and water pollution by vege-mechanical means and revegetation., and adopting engineering controls at working areas to control the escape of mercury vapor.
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman.
Typescript.
Keywords: Mineral industries -- Environmental aspects. -- Philippines -- Davao del Norte; Gold mines and mining -- Philippines -- Davao del Norte